Comparative effectiveness of delayed-release dimethyl fumarate versus glatiramer acetate in multiple sclerosis patients: results of a matching-adjusted indirect comparison. (June 2017) - Chan, Andrew; Cutter, Gary; Fox, Robert J; Xiao, James; Lewin, James B; Edwards, Michael R
Aim: Using matching-adjusted indirect comparison, we compared efficacy outcomes in patients with relapsing–remitting multiple sclerosis treated with delayed-release dimethyl fumarate (DMF) or glatiramer acetate (GA).Materials & methods: An indirect comparison of DMF (patient-level data) and GA (aggregate data) was conducted, with average baseline characteristics of DMF patients weighted to match those for GA patients. Direct comparison of DMF and GA was conducted in CONFIRM. Final results pooled the indirect and direct comparisons using meta-analysis.Results: After matching, baseline characteristics were balanced between DMF and GA patients. Compared with GA, efficacy was significantly in favor of DMF as measured by annualized relapse rate (rate ratio: 0.76; 95% CI: 0.57–1.00; p = 0.0474) and 12-week confirmed disability progression (risk ratio: 0.59; 95% CI: 0.46–0.76; p < 0.0001).Conclusion: DMF demonstrated superior clinical efficacy versus GA.